An ultraviolet completion for the Scotogenic model - Pablo Escribano (Elsevier, 2021)
The Scotogenic model is an economical scenario that generates neutrino masses at the 1-loop level and includes a dark matter candidate. This is achieved by means of an ad-hoc Z2 symmetry, which forbids the tree-level generation of neutrino masses and stabilizes the lightest Z2-odd state. Neutrino masses are also suppressed by a quartic coupling, usually denoted by λ5. While the smallness of this parameter is natural, it is not explained in the context of the Scotogenic model. We construct an ultraviolet completion of the Scotogenic model that provides a natural explanation for the smallness of the λ5 parameter and induces the Z2 parity as the low-energy remnant of a global U(1) symmetry at high energies. The low-energy spectrum contains, besides the usual Scotogenic states, a massive scalar and a massless Goldstone boson, hence leading to novel phenomenological predictions in flavor observables, dark matter physics and colliders.